Growth, inequality and labor markets in LDCs : a survey - Ayal Kimhi (Center for Economic Studies and ifo Institute (CESifo), 2004)
This paper surveys the empirical literature on the association between growth on inequality in less developed countries, with a particular emphasis on labor market inequality. Crosscountry studies failed to find a clear link from growth to inequality. Country-specific studies that focused on labor market inequality have shown that, with a few exceptions, wage inequality increases with growth. The paper argues that the methodologies used in many of the empirical applications, designed to investigate changes in labor market inequality in developed economies, should be adjusted to account for the unique properties of labor markets in LDCs.
Keywords: O40; O12; F16; 330; growth; inequality; labor markets; Einkommensverteilung; Wirtschaftswachstum; Arbeitsmarkt; Lohnstruktur; Lohndifferenzierung; Kuznets Kurve; Entwicklungsländer